Association of overweight and obesity with dietary and physical activity behaviour among school-aged children in North India: a cross-sectional study - Arifa, Quratul Ain; Kumar, Dinesh; Rafiq, Nadeema; Nabi, Tauseef (International Journal Of Community Medicine And Public Health, 2018)
Background: Childhood obesity has reached epidemic proportions in developed countries and developing countries are not far behind. This has profound public health consequence as it increases risk of persistent obesity and its complications. Changes in social and physical environment over past years have adversely influenced eating and physical activity behaviour including attitudes and behaviour of parents. The objectives of the study were to assess and compare magnitude of overweight/obesity and its association with dietary and physical activity behaviour. Methods: This cross sectional community based study was conducted in school going children of both sex aged 6-14 years in rural and urban areas of Jammu. Children were assessed for their dietary intake and dietary habits using new USDA multiple pass recall method. Physical activity was assessed using modified global physical activity questionnaire (version 2) and expressed in MET-min/day in different domains. Following anthropometric assessment BMI percentiles were obtained from WHO age and gender specific BMI charts. Results: Of 230 children studied overall overweight/obesity observed was 8.2%. More females than males were overweight and obese. Overweight and obesity was more in urban than rural areas (males: 7.4% vs. 3%, females: 16.9% vs 6.6%). Excess calorie intake, consumption of fast foods, carbonated drinks, food from school canteen and low physical activity were significantly associated with overweight and obesity. Conclusions: Unhealthy dietary practices and low physical activity significantly contribute to obesity in children and adolescents. Health and nutritional education to them and their parents along with facilities for participation in sports and physical education would help tackle the problem.